Circular letter on the actus formalis defectionis ab ecclesia catholica from the pontifical council for legislative texts: Canons 1086 §1; 1117; 1124 - Herranz Casado, Julián (Roman Replies and CLSA Advisory Opinions 2009, 2009)
"Following the promulgation of the Circular Letter on the Actus Formal is Defectionis ab Ecclesia Catholica by the Pontifical Council for Legislative Texts in March 2006, the Council received a request for further clarification on three points in the Circular Letter. "